Proceeding of the 1st International Conference on Tropical Agriculture - Isnansetyo, Alim; Nuringtyas, Tri Rini (Springer Verlag, 2017)
The proceeding of tropical agriculture is a proceeding of papers presented at the International Conference on Tropical Agriculture. Sustainability of agriculture production system is an important issue in the world, which includes all aspects of sustainable criteria, such as technical, socio-economic, and ecological aspects. This book covers sustainable tropical agriculture, sustainable tropical fisheries, sustainable tropical animal production, sustainable tropical forestry, tropical animal health, and Innovative and Emerging Food Technology and Management. The most common, challenging issues in plant, animal and fisheries production in the tropics are climate change, inefficiency production system, low technological innovation, decreasing environment quality, and the outbreak risk of pest and diseases. These issues are closely linked to the socio-economic condition of farmers as small-scale farms are dominant in this area. In addition, post-harvest technology is crucial to maintaining the high quality of products after on farm production. This volume provides the recent research and development on tropical agriculture production systems for plant, terrestrial animal and aquatic animal to establish sustainable agriculture production in the tropics.
Keywords: Agriculture -- Tropics -- Congresses.; Tropics.; elektronické knihy; electronic books